Efficacy of mesalazine at ulcerative colitis with nutritional failure - A. V. Korolyov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. To specify relation between trophological status, severity of relapse of ulcerative colitis (UC) and efficacy of 5-aminosalicylic acid (5-ASA) for achievement of clinical remission.Summary. Nutritional status plays important role for body recovery at relapse of chronic diseases, including UC. At patients with nutritional failure remission achievement time becomes longer, bed-stay duration is increased. On the other hand, overweight patients often have more severe course of UC, as it affects important pathogenic processes. This article discusses possible links between trophological status and achievement of clinical remission, as well as between nutritional failure at UC and efficacy of mesalazine monotherapy.Conclusion. More severe course of UC, long bedstay, lower mesalazine efficacy are marked at patients with nutritional failure in comparison with those scores at patients with normal trophological status. At over-weight patients in comparison with patients with normal nutritional status no significant differences in specified parameters is observed.